2011
DOI: 10.1074/jbc.m110.186932
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated Protein Kinase (AMPK) Activation and Glycogen Synthase Kinase-3β (GSK-3β) Inhibition Induce Ca2+-independent Deposition of Tight Junction Components at the Plasma Membrane

Abstract: Extracellular Ca2؉ is essential for the development of stable epithelial tight junctions. We find that in the absence of extracellular Ca 2؉ , AMP-activated protein kinase (AMPK) activation and glycogen synthase kinase (GSK)-3␤ inhibition independently induce the localization of epithelial tight junction components to the plasma membrane. The Ca 2؉ -independent deposition of junctional proteins induced by AMPK activation and GSK-3␤ inhibition is independent of E-cadherin. Furthermore, the nectin-afadin system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
44
1
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 60 publications
3
44
1
2
Order By: Relevance
“…5A,B). As previously reported (Zhang et al, 2011), the addition of Ca 2+ to the culture medium induced the interaction between I-afadin and ZO-1. The co-immunoprecipitation of I-afadin and ZO-1 was significantly increased in the presence of the R-568 compound.…”
Section: +supporting
confidence: 48%
See 4 more Smart Citations
“…5A,B). As previously reported (Zhang et al, 2011), the addition of Ca 2+ to the culture medium induced the interaction between I-afadin and ZO-1. The co-immunoprecipitation of I-afadin and ZO-1 was significantly increased in the presence of the R-568 compound.…”
Section: +supporting
confidence: 48%
“…This manipulation is referred to as a 'Ca 2+ switch', and is associated with a rise of the cytosolic concentration of Ca 2+ (Cereijido et al, 1978;Gonzalez-Mariscal et al, 1990). Previous observations from our group and others have demonstrated that the Ca 2+ switch stimulates various independent cellular cascades, including the protein kinase C (PKC), the AMP-activated protein kinase (AMPK) and the glycogen synthase kinase 3b (GSK-3b) pathways (Balda et al, 1991;Zhang et al, 2006;Zheng and Cantley, 2007;Zhang et al, 2011). In MDCK cells, a Ca 2+ switch is typically associated with the activation of AMPK and the inhibition of GSK-3b.…”
Section: +mentioning
confidence: 99%
See 3 more Smart Citations